Interaction of haemin with albumin-based macroporous cryogel: Adsorption isotherm and fluorescence quenching studies - Hajizadeh, Solmaz; Dicko, Cedric; Bülow, Leif (Frontiers in Bioengineering and Biotechnology, 2022)
Albumin-based cryogels for capturing haemin were synthesised by crosslinking different biomolecules, bovine serum albumin (BSA) and ovalbumin (OVA). The impact of the protein and coupling agent concentrations on cryogel's mechanical properties, swelling ratios and polymerisation yields, as well as autoclaving as a post-treatment on the cryogel, were studied. We found that BSA (50 mg/mL) and the crosslinker (N-(3-dimethylaminopropyl)-N’-ethylcarbodiimide hydrochloride, 46 mg/mL) formed a cryogel with optimum physical characteristics at a comparatively low protein concentration. The cryogel's mechanical stability was increased using a double-layer cryogel approach by crosslinking the BSA proteins at subzero temperature inside an acrylamide and hydroxyethyl methacrylate premade cryogels. Batch binding and kinetic adsorption isotherms of haemin on the cryogels were assessed to evaluate their binding capacity toward the porphyrin molecule. The results showed that single-layer cryogels (BSA and OVA) had a higher capacity (~0.68 mg/mL gel) and higher reaction rate constant towards haemin adsorption than double-layer gels. In contrast, the double-layer cryogels had higher mechanical strength than single-layer gels. The experimental results suggested that the cryogels followed the Freundlich model and the pseudo-second-order isotherm for batch adsorption and kinetics, respectively. The interaction between haemin and the gels was studied by fluorescence quenching. We found between 1.1 and 1.6 binding sites for different cryogels.